Eighth Five Year Plan 1992-97 Volume II Sectoral Programmes of Development - Planning Commission, Government of India (Planning Commission, Government of India, 1992)
Agriculture and allied activities constitute the single largest contributor to the Gross Domestic Product (GDP), accounting for almost 33% of the total. They, are vital to the national well-being as, besides providing the basic needs of the society and the raw materials for some of the important segments of Indian industry . they provide livelihood for almost two thirds of the work force. The share of the agricultural products in the total export earnings, both in primary and processed forms, is very significant
Government of India Planning Commission
Government of India Planning Commission
Keywords: Eighth Five Year Plan- Sectoral Programmes of Development; Economic development